Saudi Arabia : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper suggests that while the government should continue to work on clearly defining its fiscal policy objectives, at this stage the focus of reforms should be to continue to strengthen the fiscal framework rather than on introducing a formal fiscal rule. A fiscal rule is only as good as the institutions that support it. Moreover, resource rich countries' experiences with fiscal rules have been mixed as it has proven difficult to formulate rules which are simple, flexible, and robust that can withstand large commodity prices swings. One key question before the government is to define its long-term fiscal policy objectives beyond 2023. This will help determine how it may want to anchor fiscal policy. While a target for the overall balance, as announced in the Fiscal Balance Program, is a reasonable objective for the next 5 years, such a target may not deliver the longer-term fiscal goals of the government. It is also subject to swings in oil prices-it may not be achievable if oil prices decline significantly, but if oil prices were to increase substantially, the target could be achieved even if spending were to increase to such a level that increases future fiscal vulnerabilities. Therefore, it would be better to formulate fiscal policy objectives in terms of the primary non-oil balance rather than the overall balance.